Inverted Expression Profiles of Sex-Biased Genes in Response to Toxicant Perturbations and Diseases - Ung, Choong Yong (Public Library of Science, 2013)
The influence of sex factor is widely recognized in various diseases, but its molecular basis, particularly how sex-biased genes, those with sexually dimorphic expression, behave in response to toxico-pathological changes is poorly understood. In this study, zebrafish toxicogenomic data and transcriptomic data from human pathological studies were analysed for the responses of male- and female-biased genes. Our analyses revealed obvious inverted expression profiles of sex-biased genes, where affected males tended to up-regulate genes of female-biased expression and down-regulate genes of male-biased expression, and vice versa in affected females, in a broad range of toxico-pathological conditions. Intriguingly, the extent of these inverted profiles correlated well to the susceptibility or severity of a given toxico-pathological state, suggesting that inverted expression profiles of sex-biased genes observed in this study can be used as important indicators to assess biological disorders.